'Babies know the Facts about Folic': A behavioral Change Campaign utilizing Digital and Social Media - Tina Flaherty (Frontiers Media S.A., 2015)
Ireland (ROI) and Northern Ireland (NI) have high prevalence rates of Neural Tube Defects (NTD's) and evidence suggest these have increased in recent years (McDonnell, R., 2013, Department of Health Social Services and Public Safety, 2013). Folic acid supplementation prevents 72% of NTDs and it's recommended that women of childbearing age take a 400µg daily folic acid supplement for 12 weeks pre conception until the end of the first trimester (EUROCAT, 2007). The advice on the island of Ireland (IOI) has been extended to include all women of childbearing age who are sexually active and who could become pregnant to account for the fact that approx. 50% of pregnancies are unplanned (Food Safety Authority of Ireland, 2006). Although women know folic acid's function in relation to preventing NTDs, approximately 1 in 5 on the IOI report taking folic acid before pregnancy (Cawley et al., 2015; McNullty et al. 2011; safefood, 2015). These low consumption figures appear to be as a result of the misconceptions women have in relation to folic acid (Faughnan et al., 2009). These misconceptions create barriers for behavioural change. Key behavioural barriers include the belief that folic acid is only necessary during pregnancy (Mazza and Chapman, 2010), that contraception is 100% reliable and that taking folic acid is a 'tell-tale' sign that they are sexually active or planning a pregnancy (Faughnan et al., 2009). Additionally, women perceive that folic acid fortification in food provides sufficient levels and the cost and inconvenience is greater than they are willing to consider (Faughnan et al., 2009). To address the increasing rates of NTDs and the behavioural barriers to taking folic acid, safefood launched a campaign in July, 2015. The campaign entitled 'Babies Know the Facts about Folic' was carried out via digital and social media marketing, but also included public relations and stakeholder engagement. Digital and social media marketing channels were chosen because they have been shown to be a promising vehicle for delivering public health interventions with potentially greater reach, lower cost and greater longevity than in-person communications (Yang et al., 2015, McGloin & Eslami, 2014). More than 80% of citizens in ROI access the Internet daily from a variety of devices including smart phones and tablets (Google, 2015). Michie et al.'s (2011) taxonomy of behavioural change was used to identify a number of techniques deemed appropriate for this campaign. These included; information about social and environmental consequences, information about health consequences, feedback on the behaviour and feedback on outcome(s) of the behaviour. A 'Babies know the Facts about Folic' hub was designed for the safefood website and safefood's social media channels were used during the campaign to engage with women, promote discussion and distribute the campaign message. The core message was also advertised online through display advertising and in e-newsletters including major news portals, women's portals and parenting websites. Methodology An online survey was distributed pre campaign and post campaign on safefood's social media channels (Twitter and Facebook) and promoted to the target audience via social media advertising. The sample consisted of 656 women pre campaign and 738 women post campaign. The analysis was carried out using SPSS using a chi-square test for independence. Findings The campaign received significant exposure on social and digital channels. The hub on the safefood website received over 33,485 views during the duration of the campaign. The campaign had a reach of 830,389 on Facebook and an overall engagement rate on 1.62 on Facebook and 4% on Twitter. A shift in women's knowledge, attitudes and behaviours as a result of the campaign was observed. Prior to the launch of the campaign 26.4% of women believed that all sexually active women who could potentially become pregnant should ensure they are taking folic acid supplements. This increased to 74.8% post campaign (p<.001). The research also indicated that pre campaign 7.3% of women routinely took folic acid supplements although they were not planning a pregnancy, this figure increased to 14.5% post campaign indicating an increase of 6.9% (p<.001). Sales of folic acid on the island of Ireland also increased with pharmacies, retailers and manufacturers noting increases in sales of between 19% and 30%.